Respon Pertumbuhan Anakan Shorea leprosula Miq, Shorea mecistopteryx Ridley, Shorea ovalis (Korth) Blume dan Shorea selanica (DC) Blume terhadap Tingkat Intensitas Cahaya Matahari - Andi Sukendro; Eri Sugiarto (Jurnal Silvikultur Tropika, 2012)
The Growth Response of Saplings Shorea leprosula Miq, Shorea mecistopteryx Ridley, Shorea ovalis (Korth) Blume dan Shorea selanica (Dc) Blume toward Sunlight Intensity LevelMeranti is one of the commercial wood that has been recognized by many countries of Southeast Asia with a variety of trade names, especially the kind of red meranti (Shorea spp.). Red Meranti, including endemic species in Indonesian including threatened extinct namely  Shorea leprosula (Kalimantan),  Shorea ovalis (Kalimantan) and  Shorea selanica (Maluku) are entered into the IUCN Red List (Ashton 2011). The giving of shade on meranti saplings is very important in both the field and in the nursery. The giving of shade plants performed as meranti is the kind of gap opportunist in where light is a limiting factor for early growth.This research observe the growth response of red meranti saplings of S. leprosula, Shorea mecistopteryx, S. ovalis and  S. selanica with treatment  shade 0% (light intensity 100%), 20% shade (light intensity 80%), 40% shade (light intensity 60 %), 60% shade (light intensity 40%). The experiments did  with two factorial completely randomized design. The results of research treatment shade showed that red meranti saplings of S.  leprosula, S. mecistopteryx, S. ovalis, and  S. selanica real influential. The treatment shade 60% (light intensity 40%) give the best response to the growth of S. leprosula, S. mecistopteryx, S. ovalis, and S. selanica.